MAPPING KEBUTUHAN PENGEMBANGAN KOMPETENSI GURU PAI SD DI SUKOHARJO: SEBAGAI PIJAKAN DALAM MENDESAIN PROGRAM PENGABDIAN DOSEN PAI - Fauzi Muharom (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This research aimed at knowing the mapping of the needs of teacher competence development of Islamic Education teachers of the Elementary Schools in 12 districts in Sukoharjo. The data were collected through interview and documentation. The results of the research showed that the mapping of the needs of teacher competence development of the Islamic Education teachers of the Elementary Schools is learning strategies, training of classroom action research, qur’an recitation assisting, trainingof making learning media, training of information technology learning, training of making test item grids, training of making teaching materials, assisting of curriculum 2013, training of making teaching lesson plan, training of making administrationfor Islamic Education teachers, training of graphic art, training of the art of Islamic Javanese song macapat and rebana. The design of the lecturer community service for the lecturers of Islamic Education Department of IAIN Surakarta can be conducted in two kinds of designs namely focusing on the needs of teacher competence development of the Islamic Education of the Elementary Schools in one district, based on the priorityscales of teacher competence development of Islamic Education of the Elementary Schools in Sukoharjo.